Reducing grain damage in naked oat through gentle harvesting - Kirkkari, Anna-Maija; Peltonen-Sainio, Pirjo; Rita, Hannu (MTT Agrifood Research Finland, 2001)
Paljasjyväinen kaura on altis sadonkorjuun aikaisille itävyysvaurioille varsinkin kun sato joudutaan puimaan kosteana. Työtehoseuran koetilalla Rajamäellä testattiin paljasjyväisellä kauralla puinnin aiheuttamia itävyysvaurioita eri puintikosteuksissa vuosina 1998-2000. Kun puintikosteus lisääntyi, paljasjyväisen kauran itävyys heikkeni enemmän kuin tavanomaisen kauran. Kosteana puitujen paljasjyväisten kaurojen itävyys oli lähes 20 prosenttiyksikköä alempi kuorelliseen kauraan verrattuna. Itävyysvaurioita pystyttiin alentamaan paljasjyväisellä kauralla vähentämällä puintikelan kierrosnopeutta 1200 kierroksesta/min (28 m/s) 900 kierrokseen (21 m/s). Saatu tulos ei kuitenkaan ollut tilastollisesti merkitsevä. Puintivälin kiristämisellä ei sen sijaan ollut vaikutusta itävyystuloksiin. Tulosten perusteella paljasjyväinen kaura on puitava mahdollisimman kuivana (alle 20 % kosteudessa) itävyyden säilyttämiseksi. Puintikelan kierrosnopeutta alentamalla itävyysvaurioita voidaan välttää korkeammissakin kosteuksissa.

The caryopsis of naked oat is sensitive to mechanical damage at harvest, especially at high grain moisture content. For producing high quality naked oat seed, it is recommended that harvesting be carried out at as low grain moisture content as possible. This reduces mechanical damage to the grain and promotes germination. Under northern growing conditions, grains are often harvested at 20% moisture content or higher. In this study, reduced grain resulted from using gentler settings on the combine harvester. Two naked oat cultivars and one conventional oat were harvested at different grain moisture content using three combine harvester settings: the first setting that recommended for conventional oat, the second a reduced cylinder speed and the third a narrow concave clearance. The greater the grain moisture content of naked oat at harvest, the more damage was caused by threshing. Lower cylinder speeds tended to result in better germination than higher speeds, even under moist conditions. Narrowing the concave clearance did not affect germination.
Keywords: Ka; naked oat; threshing; germination; moisture content; cylinder speed; concave clearance